A study on mental health and its influencing factors among police officers during the COVID-19 epidemic in China - Wu, Ji; Wu, Qiong; Xia, Minghui; Xiao, Jing; Yan, Xin; Li, Dao (Frontiers in Psychiatry, 2023)
Background: The outbreak of the COVID-19 pandemic has had a tremendous impact on people’s health and well-being. The crisis also threw into sharp relief the fact that police officers faced an increased risk of developing mental health problems. The main purpose of this study was to explore the effects of work stress and risk perception on the mental health of police officers during the epidemic. Methods: We conducted a cross-sectional online survey among police officers in Wuhan city, China, and data were collected from March 11 to May 12, 2022. A total of 358 questionnaires were received, of which 302 were considered valid. The questionnaires included demographic information, work stress scale, SCL-90 scale and epidemic risk perception scale. Descriptive analyses, one-way analysis of variance and linear regression were used to analyse the data. Results: The prevalence of mental health problems was 38.74% among the surveyed police officers. The results indicated that the total score of SCL-90 and its subdimensions were positively correlated with work stress and risk perception. Moreover, we found that three factors were relevant to the police’s mental health: age, marital status and education. Conclusion: Front-line police officers tend to show a higher prevalence of symptoms of mental disorders during the COVID-19 pandemic. We found that increased work stress and risk perception can adversely affect officers’ mental health. Consequently, policy-makers and police organizations should establish an internal mental health problem coping team to improve police officers’ mental health resilience.